The Clinical Correlates of Reported Childhood Sexual Abuse: An Association Between Age at Trauma Onset and Severity of Depression and PTSD in Adults - SCHOEDL, ALINE FERRI (2010)
This study investigated the relationship between the age of self-reported sexual abuse occurrence and the development of post-traumatic stress disorder and/or depressive symptoms in adulthood. Subjects were evaluated for the presence of post-traumatic stress disorder and/or depressive symptoms as well as for a self-reported history of sexual abuse before the age of 18. Results found that relative risk of having severe post-traumatic stress disorder symptoms was 10 times higher in patients reporting sexual abuse after age 12 than in those reporting sexual abuse before age 12. Relative risk of having severe depressive symptoms was higher for those abused before the age of 12 than for those abused after the age of 12. Findings suggest that the impact of reported sexual abuse at different stages of development may lead to distinct psychiatric symptoms in adulthood.